Rhabdomyosarcoma in Adults: Case Series and Literature Review - Chen J; Liu X; Lan J; Li T; She C; Zhang Q; Yang W (Dove Medical Press, 2022)
Jian Chen,1 Xiaoyun Liu,1 Jian Lan,1 Tingchao Li,2 Chaokun She,1 Qingyun Zhang,1 Wei Yang3 1Department of Gynecology and Obstetrics, The Third Affiliated Hospital of Zunyi Medical University (The First People's Hospital of Zunyi), Zunyi City, Guizhou Province, People's Republic of China; 2Pathology Department, The Third Affiliated Hospital of Zunyi Medical University (The First People's Hospital of Zunyi), Zunyi City, Guizhou Province, People's Republic of China; 3Imaging Department, The Third Affiliated Hospital of Zunyi Medical University (The First People's Hospital of Zunyi), Zunyi City, Guizhou Province, People's Republic of ChinaCorrespondence: Xiaoyun Liu; Jian Lan, Department of Gynecology and Obstetrics, The Third Affiliated Hospital of Zunyi Medical University (The First People's Hospital of Zunyi), No. 98, Fenghuang Road, Zunyi, Guizhou, 563000, People's Republic of China, Email 656479556@qq.com; 1981551873@qq.comAbstract: Rhabdomyosarcoma, a common soft tissue malignant tumor in children and adolescents, is exceedingly rare in adults. Nevertheless, The outcome in adults is very poor, especially when compared to outcomes in children in whom significant improvements in treatment has been achieved. The first case was of a 24-year-old pregnant Chinese woman with a rare primary site of rhabdomyosarcoma in the perineal body. She presented with a perineal mass and was diagnosed during the second trimester of pregnancy, which is a very rare occurrence. The second case was a 70-year-old Chinese woman who suffered from right lower abdominal pain for 1 month and was misdiagnosed with an epithelial ovarian carcinoma. Mesenteric pleomorphic rhabdomyosarcoma was later confirmed by postoperative pathology. Both cases had undergone preoperative examination with chest and abdominal computed tomography (CT) and pelvic magnetic resonance imaging (MRI) examinations, as well as examination of complete blood count, liver panel, renal panel, and serum tumor markers. Diagnosis was based on histopathology and immunohistochemistry. The patient in the first case received chemotherapy after which the mass decreased in size; however, the patient was lost to follow-up. The second case underwent tumor resection and received chemotherapy and radiotherapy.Keywords: rhabdomyosarcoma, adult, pregnancy, diagnosis, heterogeneity, prognosis